RENCANA BISNIS BRAINWASH LAUNDRY EXPRESS MENGOPTIMALKAN PELAYANAN DAN PENGALAMAN PELANGGAN - Abdilah, Egi Mardiana; Hendri, Meriza (POLITEKNIK LP3I JAKARTA, 2026)
Brainwash Laundry Express Shoes is a professional shoe cleaning and care service located in Bandung. This business was established to meet the growing demand for shoe cleaning and care among urban communities, particularly students, office workers, and sneakerhead communities. With its Express Service concept, pick-up and delivery service, and maintenance consultation, Brainwash prioritizes speed, cleanliness, and quality results. Bandung, as a creative city and center of lifestyle trends, is a strategic location for the development of this business. With an initial capital of IDR 150 million, this business is projected to reach its break-even point in 10–12 months, with a monthly revenue target of IDR 30–50 million and a net profit margin of 25–30%. The results of Porter's Five Forces analysis show that Brainwash has a great opportunity to compete through service differentiation, professional quality, and superior customer experience. The threat of competitors and substitute products can be overcome through digital innovation, friendly service, and customer loyalty programs. By focusing on service quality and customer comfort, Brainwash Laundry Express has strong growth potential and can develop as a lifestyle brand that is relevant to the urban community of Bandung.